1999
DOI: 10.1080/02724939992167
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal swabs for diagnosing tuberculosis

Abstract: The value of smear and culture of laryngeal swabs as a method of confirming pulmonary tuberculosis was investigated in Indian children. A total of 116 children with 'suspected' tuberculosis had a Mantoux test and chest X-ray. Of these, 51 had a positive Mantoux and/or chest X-ray compatible with tuberculosis, and this group had two laryngeal swabs taken on each of 3 consecutive days. The Mantoux test was positive in 37 (73%) of the 51 'probable' cases. Chest X-ray was abnormal in 36 (71%) cases and compatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…21 A recent study of laryngeal swabs in Indian children found a positive smear/ culture in 33%. 22 The yield from examining laryngeal swabs in this study was very low.…”
Section: Discussionmentioning
confidence: 94%
“…21 A recent study of laryngeal swabs in Indian children found a positive smear/ culture in 33%. 22 The yield from examining laryngeal swabs in this study was very low.…”
Section: Discussionmentioning
confidence: 94%
“…In this case, positive findings on chest radiographs helped in making a provisional diagnosis and initiating treatment. Acid‐fast smear and culture of laryngeal swabs is of value in confirming pulmonary tuberculosis in cases of negative sputum smears [15].…”
Section: Discussionmentioning
confidence: 99%
“…From included manuscripts (appendix pp 26–33 for study characteristics; appendix p 5 includes full methodological details and results by study), we classified types of upper respiratory tract sampling into four groups: laryngeal swabs (32 studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ), nasopharyngeal aspirate (ten studies 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ), oral swabs (18 studies 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ), and other (mouthwash three studies, 71 , 72 , 73 nasal swabs one study, 74 saliva four studies, 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%